College writing skills - Langan, John (McGraw Hill, 2000)
Designed to help students master essay writing, this work provides a wide variety of assignments and activities, both structured and open-ended. It focuses on the four essentials of writing - unity, support, coherence and sentence skills - as keys to effective writing.